2002
DOI: 10.2105/ajph.92.2.280
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized HIV Infection Among Patients Attending Sexually Transmitted Disease Clinics

Abstract: HIV infection is unrecognized in substantial numbers of patients with HIV infection visiting STD clinics. Efforts are needed to increase HIV testing and counseling of all patients visiting these clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 12 publications
2
39
0
Order By: Relevance
“…Weinhardt demonstrated increased self-perception of risk after a detailed sexual behavioral interview, suggesting increased motivation for subsequent behavioral change [10], including VCT. However, Weinstock found that STD clinic patients not tested for HIV were more likely to be positive, suggesting those at highest risk avoid voluntary testing [11].…”
Section: Discussionmentioning
confidence: 99%
“…Weinhardt demonstrated increased self-perception of risk after a detailed sexual behavioral interview, suggesting increased motivation for subsequent behavioral change [10], including VCT. However, Weinstock found that STD clinic patients not tested for HIV were more likely to be positive, suggesting those at highest risk avoid voluntary testing [11].…”
Section: Discussionmentioning
confidence: 99%
“…1 Although African Americans represent 13% of the U.S. population, they account for approximately 45% of new HIV infections, and the rate of HIV infection among African Americans is seven times that of white Americans. 1 Individuals who do not know their HIV status may unknowingly transmit the virus [2][3][4][5][6] ; more than half of new infections in the United States are spread by HIV-positive individuals who do not know they are infected. 7,8 Several studies have found that knowing one's HIV status can lead to a reduction in highrisk sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…26 For example, in order to differentiate themselves from high-risk groups, some individuals underestimate their risk of contracting a stigmatized illness, such as HIV or other sexually transmitted diseases. 27 The underestimation of perceived risk often translates into lower rates of testing and treatment for stigmatized conditions, and poses a significant barrier to preventative behaviors. 28 A growing body of research throughout the world indicates that greater HIVrelated prejudice (i.e., ''People who have AIDS are dirty'' ''I do not want to be friends with someone who has AIDS'') is associated with decreased HIV testing rates.…”
mentioning
confidence: 99%